2016
DOI: 10.12681/mms.1770
|View full text |Cite
|
Sign up to set email alerts
|

Dinoflagellate cysts production in the north-western Adriatic Sea

Abstract: A sediment trap study was conducted in the Gulf of Venice, north-western Adriatic Sea, from April to December 2005 to assess relationships between planktonic dinoflagellates and cyst production. Every month, CTD profiles and discrete samplings for phytoplankton, nutrients and particulate matter were conducted. Cyst fluxes spanned from 90 to 127,600 cysts m-2 d-1 and major peaks were due to a small cyst attributed to cf. Biecheleria and to calcareous cysts of Scrippsiella trochoidea. A good correspondence betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…For example, Biecheleria spp. was reported in NW region (Bastianini et al, 2016), but was undetected in port of Venice during this study, whereas Protoperidinium conicum was reported in mE region (Viličić et al, 2002), but was observed only in port of Split during this study (and not in port of Šibenik).…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…For example, Biecheleria spp. was reported in NW region (Bastianini et al, 2016), but was undetected in port of Venice during this study, whereas Protoperidinium conicum was reported in mE region (Viličić et al, 2002), but was observed only in port of Split during this study (and not in port of Šibenik).…”
Section: Discussionmentioning
confidence: 44%
“…Spreading of dinoflagellates over coastal areas, and across the Adriatic by natural pattern, by general circulatory system and/or large gyres connecting western and eastern part of Adriatic, seems to be rather limited. Nevertheless, three taxa were observed in a new region during this study, whereto the spreading might have occurred by general anticyclonic currents system: Scrippsiella precaria spread from SE (Saracino and Rubino, 2006b;Rubino et al, 2009) up the eastern coast to NE (observed in port/s of Trieste and Koper), and Protoperidinium claudicans down the western coast, from NW (Sangiorgi and Donders, 2004;Bastianini et al, 2016) down to SW (observed in port of Bari). Protoperidinium compressum, observed in port of Split might have spread by large gyres eastwards from mW (Rubino et al, 2000) and/or SW (Rubino et al, 2002(Rubino et al, , 2009 and then up the eastern coast by general anticyclonic system.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation